A simple adaptive fuzzy logic controller base on shifting of the membership function - Fatimatul Anis, Bakri; Mohd Yusoff, Mashor, Prof. Dr.; Siti Maryam, Sharun; Norhayati, M. N.; Supardi, N. Z.; Zuraidi, Saad (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/